INFLUENCE OF PSYCHOPHYSICAL COMPETENCE ON CAPACITY AND INTELLECTUAL ACTIVITY OF MEDICAL STUDENTS - Губка, П.І.; Emets, A.V.; Skrinnik, E.O. (World of Medicine and Biology, 2015)
The individualization of realization of studies, improvement of ability to work and intellectual activity, motivations to studies by physical exercises are studied in the article. Development and support of certain level is considered professionally important psychical and physical qualities. The students of medical academy took part in an experiment. Together with other physical exercises the special attention was spared to the special respiratory exercises. Facilities of physical culture and sport, are showed, they promote a general and special professional physical capacity. Resulted methods of combination of the correctly organized breathing and psychological tuning as to the mean of salutary influence on organizm. It is set that exercises are offered by us instrumental in an improvement professionally of important psychological and physical qualities, and also increase of capacity and intellectual activity of students of physicians, removal of psychological and nervous tension.
Keywords: the problem of health; individual approach; psychophysical training; abilility to work